2012
DOI: 10.3174/ajnr.a3180
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Arteriovenous Malformations: Results of Ethanol Sclerotherapy

Abstract: BACKGROUND AND PURPOSE:Peripheral AVM is a locally aggressive disease with a high tendency to recur; its treatment is complex, especially in the anatomically delicate head and neck area. Here, we report results of ethanol sclerotherapy for head and neck AVM and discuss its potential use for peripheral AVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 41 publications
1
55
0
2
Order By: Relevance
“…They are composed of dysmorphic arterial and venous connections without an intervening capillary bed. [5,6] They develop early in fetal life due to defective retiform plexus formation. Thus, they are seen in early fetal development itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are composed of dysmorphic arterial and venous connections without an intervening capillary bed. [5,6] They develop early in fetal life due to defective retiform plexus formation. Thus, they are seen in early fetal development itself.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical condition progress as a result of shunting of blood between high pressure arteries low pressure veins. [5][6][7] A number of cases of AVMs have been described by different authors. 81 cases of head and neck AVMs were reported by Kohout et al The most of AVMs are found in cheek (31%), ear (16%), and nose (10%).…”
Section: Discussionmentioning
confidence: 99%
“…Coils, including stainless steel coils, platinum coils or detachable coils, are typically used as one of the most common embolization agents to embolize the AVMs alone, to embolize the expanded tortuous reflux veins or to eliminate the AVMs combined with absolute ethanol or other embolization agents (3).…”
Section: Introductionmentioning
confidence: 99%
“…With its progression, AVM is capable of destroying normal tissues and can lead to complications, for instance severe disfigurement, unmanageable bleeding, ulceration, pain and cardiac volume overload. 5 Initially lesions are recognized based on the prevailing vascular structure involved-arterial, venous, lymphatic, or capillary, considering arterio-venous shunting and also the combined vascular defects. The embryological background of the lesion is then considered for additional demarcation.…”
Section: Introductionmentioning
confidence: 99%